PERBEDAAN PENGGUNAAN MATA PANCING DAN JAKET TUNA TERHADAP KECEPATAN PENARIKAN HASIL TANGKAPAN TUNA (Thunnus albacares) DENGAN ALAT TANGKAP PANCING ULUR DI PERAIRAN SUKABUMI, JAWA BARAT - Kristiawan, Hendrik Ari; Boesono, Herry; Fitri, Aristi Dian Purnama (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Tuna jacket in appliance assist handling at the time of tuna caught with fishing rod postpone which attached or utilized by fish-hook time of fishing rod postpone capture target fish hooking, functioning as a means of protector or eaten of haul fish to be preyed or eaten by other fish and tie down peripatetic capture fish to be quickly become death.Purpose of this research is to know and analyse influence of usage of appliance assist in the form of tuna jacket to time withdrawal of fish haul of tuna and know difference of tuna haul by using optometry fish between number 2 and number 5. Method which used in this research that is eksperimental because data not yet been obtained and not yet made available so that variable to be measured have to be awakened its data pass attempt, observation to new data can be run after conducted the attempt.Result of from method of experimental obtained bydata which to show that caught fish use tuna jacket can be pulled with short meter if compared to if without using appliance assist the because [at] appliance assist the tuna jacket can close tuna gill fin in order not to be open so that gill moment closed hence fish incapable of breathing and will quickly weaken easier so that for haul. While for the difference of fishing rod eye don't have influence because its true result of which got much the same to.